The use of ict by sme's in Zambia to access business information services and investments: Barriers and drivers - Martin Mwila; Luka Ngoyi (Journal of Global Entrepreneurship Research, 2019)
The research aimed at answering key questions regarding the use of ICTs among SMEs in their businesses with an analysis and consideration of the possible factors that enable ICTs to be valued, as drivers and the possible factors that deter them not to be recognised as business development agents to be the barriers. The research was conducted on a sample of 60 SMEs with no formal business registration and 40 SMEs with formal business registration with a response of 76.7% and 87.5% respectively. Results disclosed that ICTs are a major aspect in business operations, formally and informally with the major drivers happening to be the reduction in cost and ease of doing business. The major challenges were the expense at which ICTs come with and the poor ICT infrastructure. There is a relation between the investment in ICTs in businesses with the increase in productivity as 67.04% of the respondents confirming the effect of implementation. The study recommends that Government fully implements the framework for ICTs laid in its Seventh National Development Plan (7NDP) to make ICTs available for socio-economic development through infrastructure development, reduction on taxes laid on ICT related goods and through Public-Private Partnerships (PPPs) that seek to enhance the communication.
Keywords: 650; Small and Medium enterprises (SMEs); Drivers; Barriers; Information communication technologies (ICTs)